Boganmeldelse. Dahl, R.og Sveian, H. (red.): Ka dokker mein førr stein! Geologi, landskap og ressurser i Troms, 154 sider. NGU, 2004. - Nielsen, Jan Kresten; Nielsen, Jesper Kresten (Varv, 2004)
Intet resumé